PENERAPAN PROBLEM BASED LEARNING BERBANTUAN APLIKASI GEOGEBRA UNTUK MENINGKATKAN BERFIKIR KREATIF MATEMATIS SISWA - VINA LUSIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The problem of students in learning mathematics is the low literacy skills of the participants in translating mathematical problems in the form of text into mathematical symbols, sometimes students do not understand what the reading text means. This is caused by several factors, including related to the learning strategy implemented by the teacher and the media used is not appropriate for the material presented so that students' mathematical thinking skills are not well developed. Based on these problems, the researcher conducted research with the title application of problem based learning assisted by the GeoGebra application to improve students' mathematical thinking in the matter of two-variable Linear inequalities systems. This research was conducted in grade X SMA Islam Nurul Fikri Boarding School Lembang. The subjects in this study were students of class X3 and X4 SMA Islam Nurul Fikri Boarding School Lembang with a total of 40 female students. The approach taken by researchers in this study uses a quantitative approach. From the results of the pre-test and post-test students' mathematical ability data for the experimental class the ability to think mathematically during the post-test increased from the pre-test results with an increase of 19% and for students' very mathematical thinking abilities in the pre-test only 0% but after applying the model PBL with GeoGebra post-test scores increased to 42% which is a huge change. While the control class from pre-test to post-test did not change significantly. From the results of data analysis, the value (sig.2-tailed) with the t-test was 0.005. While the value (sig.1-tailed) is 0.0025.The Value is 0.0025 < 0.05. Thus the null hypothesis (Ho) is rejected, which means the alternative hypothesis (H1) is accepted. Therefore, students' mathematical creative thinking abilities taught problem based learning (PBL) model with the Geogebra are better than students' mathematical creative thinking abilities taught problem based learning (PBL) learning model on the matter of a two-variable linear inequality system. ABSTRAKPermasalahan siswa dalam pembelajaran matematika adalah rendahnya kemampuan literasi peserta dalam menerjemahkan masalah matematika dalam bentuk teks kedalam simbol matematika, terkadang siswa tidak memahami apa maksud dari teks bacaan tersebut. Hal ini disebabkan oleh beberapa faktor, antara lain berkaitan dengan strategi pembelajaran yang dilaksanakan guru dan media yang digunakan belum tepat guna terhadap materi yang disampaikan sehingga kemampun berfikis matematis siswa tidak terbagun dengan baik, Berdasarkan permasalahan tersebut, maka peneliti melakukan penelitian dengan judul penerapan problem based learning berbantuan aplikasi GeoGebra untuk meningkatkan berfikir matematis siswa pada materi sistem pertidaksamaan Linear dua Variabel. Penelitian ini dilaksanakan dikelas X SMA Islam Nurul Fikri Boarding School Lembang Adapun subjek dalam penelitian ini adalah siswa kelas X3 dan X4 SMA Islam Nurul Fikri Boarding School Lembang dengan jumlah 40 siswa perempuan. Pendekatan yang dilakukan oleh peneliti dalam penelitian ini menggunakan pendekatan kuantitatif. Dari hasil data kemapuan matematis siswa pre-test dan post test untuk kelas eksperimen kemampuan berfikir matematis saat post test meningkat dari hasil pre-test dengan peningkatan sebesar 19% dan untuk kemampuan berfikir sangat matematis siswa di pre-test hanya 0% namun setelah penerapan model PBL berbantuan GeoGebra nilai post test meningkat menjadi 42% perubahan yang sangat besar. Sedangkan kelas control dari pre-test ke postes tidak terjadi perubahan secara signifikansi. Dari hasil analisis data diperoleh nilai (sig.2-tailed) dengan uji-t dua pihak adalah 0,005. Sedangkan nilai (sig.1-tailed) adalah 0,0025. Nilai 0,0025< 0,05. Dengan demikian Hipotesis nihil (Ho) ditolak yang berarti Hipotesis aternatif (H1) diterima. Oleh karena itu kemampuan berpikir kreatif matematis siswa yang diajarkan dengan model pembelajaran problem based learning (PBL) berbantuan Geogebra lebih baik daripada kemampuan berpikir kreatif matematis siswa yang diajarkan dengan model pembelajaran problem based learning (PBL) tanpa berbantuan Geogebra pada materi sistema pertidaksamaan linear dua variable (SPtLDV).